2014
DOI: 10.3746/pnf.2014.19.2.089
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-inflammatory Activities of Broccoli Florets in LPS-stimulated RAW 264.7 Cells

Abstract: Broccoli (Brassica oleracea var. italia) florets were extracted with 80% methanol and the extract was sequentially fractionated with n-hexane, ethyl acetate, n-butanol, and distilled water. The extract and the fractions were evaluated for total phenolic content, sulforaphane content, antioxidant activity, and anti-inflammatory activity in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. The total phenolic content and sulforaphane content of the ethyl acetate fraction (EF) were 35.5 mg gallic acid equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 30 publications
7
32
0
Order By: Relevance
“…8 , the hydroxyl radical scavenging activity of GANPs was 2 times higher than that of GA at concentrations ranging between 31.5 and 500 µg/mL with IC 50 values of 56.03 µg/mL and 105.53 µg/mL, respectively ( P < 0.05). This result also confirmed that gallic acid maintained its antioxidant properties that were consistent with other reports 32 . Gallic acid was reported to have cyclooxygenase 2 (COX-2) and nitric oxide synthase (iNOS) inhibitory properties in LPS-induced RAW 264.7 cells modulating the pro-inflammatory cytokines such as IL-17, IFN-γ, and TNF-α 33 .…”
Section: Discussionsupporting
confidence: 93%
“…8 , the hydroxyl radical scavenging activity of GANPs was 2 times higher than that of GA at concentrations ranging between 31.5 and 500 µg/mL with IC 50 values of 56.03 µg/mL and 105.53 µg/mL, respectively ( P < 0.05). This result also confirmed that gallic acid maintained its antioxidant properties that were consistent with other reports 32 . Gallic acid was reported to have cyclooxygenase 2 (COX-2) and nitric oxide synthase (iNOS) inhibitory properties in LPS-induced RAW 264.7 cells modulating the pro-inflammatory cytokines such as IL-17, IFN-γ, and TNF-α 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Treating macrophages with OBE before the stimulation with LPS partly counteracted such responses by about 30%. These results are similar to findings from recent studies demonstrating anti-inflammatory properties of polyphenols and other plant bioactives in cell cultures [52; 53] and farm animals [54]. Furthermore, our in vivo and in vitro results indicate that inhibition of IL1B production is a key component of the OBE anti-inflammatory action.…”
Section: Discussionsupporting
confidence: 92%
“…The TPC of each extract was determined using Folin‐Ciocalteu's method (Hwang and Lim ). A total of 200 μL of the extract, 800 μL distilled water, and 100 μL 2 M Folin‐Ciocalteu phenolic reagent were combined in a glass vial and mixed by vortexing.…”
Section: Methodsmentioning
confidence: 99%